H19 promotes aerobic glycolysis, proliferation, and immune escape of gastric cancer cells through the microRNA‐519d‐3p/lactate dehydrogenase A axis. Issue 6 (7th April 2021) - Sun, Linqing; Li, Juntao; Yan, Wenying; Yao, Zhendong; Wang, Ruoqin; Zhou, Xiaojun; Wu, Hongya; Zhang, Guangbo; Shi, Tongguo; Chen, Weichang
Abstract: Long noncoding RNAs (lncRNAs) have been investigated in multiple human cancers including gastric cancer (GC). Our research aims to explore the role of H19 in aerobic glycolysis, proliferation, and immune escape of GC cells. The expression of H19 in GC samples was analyzed using Gene Expression Profiling Interactive Analysis, Gene Expression Omnibus data, and real‐time quantitative PCR analysis. Relative quantification of glucose consumption and lactate production from cell supernatant were applied to assess the aerobic glycolysis of GC cells. Subcellular fractionation, luciferase reporter, and western blot assays certified the binding between genes. Cell Counting Kit‐8 and colony formation assays were used to determine GC cell proliferation. Flow cytometry, ELISA, and real‐time quantitative PCR assays were applied to analyze the immunosuppressive effect of H19. H19 was highly expressed in samples of patients with GC, and associated with tumor growth in vivo. H19 knockdown suppressed glucose consumption, lactate production, and proliferation of GC cells by regulating the microRNA (miR)‐519d‐3p/lactate dehydrogenase A (LDHA) axis. Both miR‐519d‐3p depletion and LDHA overexpression could reverse the H19 knockdown‐induced decrease in aerobic glycolysis and proliferation. Moreover, conditioned medium from stable knockdown H19 GC cells modulated the activity of immune cells including γδT cells, Jurkat cells, and tumor‐associated macrophages in a miR‐519d‐3p/LDHA/lactate axis‐dependent manner. The H19/miR‐519d‐3p/LDHA axis mainly contributed to aerobic glycolysis, proliferation, and immune escape of GC cells. Abstract : Our results showed that H19 modulated aerobic glycolysis, proliferation, and immune escape of gastric cancer cells through the miR‐519d‐3p/LDHA axis.